Regimes of language and light in J. S. Le Fanu's 'Green Tea'. Issue 7 (9th August 2019) - Dowd, Garin
ABSTRACT: While positioning and contextualising the short story 'Green Tea' by Joseph Sheridan Le Fanu (1814–1873) in relation to existing Le Fanu scholarship, this article seeks to explore further the textual reflexivity for which it is renowned. The regimes of language and light (a formulation loosely derived from the work of Michel Foucault) are presented in Le Fanu as intertwined, yet each is also presented as paradoxically set apart. Le Fanu's tale displays the discontinuity and mutual exteriority of the regimes in the form of an experimental exploration within the form of the tale itself. Through an attention to the interrelationship of the scopic and textual (and, to a lesser extent, the auditory) regimes of 'Green Tea', and to the manner in which writing is explicitly figured as both the source of disjunction and the site of interpenetration of the regimes, it is proposed that a specific understanding of allegory (in a semantic register drawing on work by Walter Benjamin and Paul de Man) can provide a fresh perspective on 'Green Tea' as an archive of the regimes of language and light of its time.